Total Synthesis of (+)-Pinellic Acid - Sunnam, Sunil Kumar; Prasad, Kavirayani R. (Synthesis, 2013)
A straightforward strategy for the synthesis of (+)-pinellic acid in 16% overall yield and 13 steps, starting from (1R)-1-(furan-2-yl)hexan-1-ol, is described. Key reactions in the synthesis include a Sharpless kinetic resolution, oxidation of a protected furan to reveal a but-2-ene-1,4-dione moiety, and an asymmetric reduction.
Keywords: pinellic acid; furan oxidation; natural products; total synthesis